DYNAMICS OF INDICATORS CARIES IN CHILDREN WITH VARYING FREQUENCY OF ACUTE RESPIRATORY VIRAL INFECTION DURING PREVENTIVE MEASURES - L. Kaskova; O. Pavlenkova (Ukrainian Medical Stomatological Academy, 2015)
Article is devoted to dynamics of indicators of dental caries in children with varying frequency of acute respiratory viral infections in the process of prevention. Under our supervision there were 80 children aged 6-7 years who were divided into 4 groups of observation. 1 - is practically healthy children suffering from ARVI 1-2 times a year, 2, 3 and 4 groups - children, who often suffer from respiratory viral infections (3-4). During 1.5 years when the children were under our supervision was 3 courses for preventive measures and conducted three examinations of children. Survey conducted to study the performance of caries intensity at 1 year and 1.5 years. Children 1 group 2 was administered only oral hygiene. Children 3 groups appointed complex that included the drug «Osteovit» use of preventive dental elixir «Sanodent» multivitamin preparation «Kinder biovital gel», use toothpaste «Dragon». Children 4 groups administered offered us a set of preventive measures, which included the use of antiviral drugs and containing calcium «Lecithin D3», «Biotryt C», multivitamin complex «Supervit» mouthwash «Lizodent», use calcium containing toothpaste. During the 2 examination, one year after the first 2 times when children have appointed preventive systems revealed increase in the intensity of caries in all groups observation. The largest increase (0,97 ± 0,02 teeth) found in children 2 groups, which often suffer from ARVI and were administered only oral hygiene. In children, one of which is almost healthy and recommended that only use items and hygiene products also marked a significant increase in the intensity of caries - on 0,78 ± 0,07 teeth. Significantly better marks in the examination of three children (0,51 ± 0,04 teeth), which has appointed renowned health care complex, aimed at increasing the resistance of dental hard tissues. The best result - 0,21 ± 0,02 teeth - in children 4 groups observing that used for the prevention of our proposed complex that included to use antiviral drugs and calcium containing «Lecithin D3», «Biotryt C», multivitamin complex «Supervit» mouthwash «Lizodent», use calcium containing toothpaste. The same trend of changes of intensity of caries in groups of children survived during the 3 examination. The largest increase was observed for 1.5 years in children 2 groups (1,35 ± 0,22), which often suffer from ARVI and were administered only oral hygiene, and the smallest (0,49 ± 0,02) - 4 groups, were administered, we proposed a set of preventive measures. Preventive expected effect in children 3 and 4 observations, which were carried out prophylactic measures. 3 In the group of children who were administered health care complex, consisting of the drug «Osteovit», mouthwash «Sanodent», multivitamin preparation «Kinder biovital gel», toothpaste «Dragon» it was 34,1% compared 2 groups and 16 % - relative to group 1 observation. Preventive effect in children 4 groups is relatively better and 2 groups - 63,7% and 53,8% compared one group of children. This result points to the positive impact of our proposed complex that includes to use antiviral drugs and calcium containing «Lecithin D3», «Biotryt C», multivitamin complex «Supervit» mouthwash «Lizodent», use calcium containing toothpaste on the resistance of solids teeth children, who often suffer from respiratory viral infections. So, children often suffer from acute respiratory viral infections after preventive measures studied parameters were better in the groups of children who were offered caries prevention systems. Especially positive trend observed in children 4 groups who used our proposed complex that includes to use antiviral drugs and calcium containing «Lecithin D3», «Biotryt C», multivitamin complex «Supervit» mouthwash «Lizodent», use calcium containing toothpaste.